Diversity of Sea Urchins on the Samboang Beach, Bulukumba District - Endang Kurniati; Andi Mu'nisa Syamsu; Andi Faridah Arsal (Bionature, 2023)
The aim of this research is to determine the diversity of sea urchins found in the waters of Samboang Beach, Bulukumba Regency. This research method uses a line transect method with a size of 1 m x 1 m. The data obtained was then identified, then analyzed using the diversity index (H'), evenness index (C) and dominance index (D). The results show that the number of sea urchin species found on Samboang Beach, Bulukumba Regency is 4 species consisting of Echinometra oblonga, Echinometra mathaei, Echinometra viridis, and Diadema setosum. The sea urchin diversity category is classified as medium, namely 1.25. The dominance index is relatively low, namely 0.31, and the evenness index is relatively stable, namely 0.903.